A Study on Reduced Air Resistance Acting on Hull of a Cargo River Ship by Used CFD - Ngo, Van He (Old Journal, 2018)
Aiming to improvement of the inland water transportation efficiency, this paper presents development of new hull concept for the cargo river ships with reduced air resistance by using a commercial CFD (Computational Fluid Dynamic) method. The CFD results of aero-dynamic performances of the ship as pressure distribution, velocity flow around hull and air resistance acting on hull are investigated by the CFD. By analysing air resistance acting on a conventional cargo river ship which is widely used in Vietnam, a new concept of cargo river ships with drastically reduced air resistance hull form has been developed. A suitable method for application of the obtained research results has been suggested namely gradual replacement the current hull form by the newly developed one.